Clinical Pharmacokinetics and Pharmacodynamics of Atezolizumab in Metastatic Urothelial Carcinoma. Issue 2 (9th June 2017) - Stroh, M; Winter, H; Marchand, M; Claret, L; Eppler, S; Ruppel, J; Abidoye, O; Teng, SL; Lin, WT; Dayog, S; Bruno, R; Jin, J; et al.
Abstract : Atezolizumab, a humanized immunoglobulin G1 (IgG1) monoclonal antibody targeting human programmed death‐ligand 1 (PD‐L1), is US Food and Drug Administration (FDA) approved in metastatic urothelial carcinoma (MUC) and is being investigated in various malignancies. This analysis based upon 906 patients from two phase I and one phase II MUC studies, is the first report of the clinical pharmacokinetics (PK) and pharmacodynamics (PD) of atezolizumab. Atezolizumab exhibited linear PK over a dose range of 1–20 mg/kg, including the labeled 1, 200 mg dose. The clearance, volume of distribution, and terminal half‐life estimates from population pharmacokinetic (PopPK) analysis of 0.200 L/day, 6.91 L, and 27 days, respectively, were as expected for an IgG1. Exposure‐response analyses did not identify statistically significant relationships with either objective response rate or adverse events of grades 3–5 or of special interest. None of the statistically significant covariates from PopPK (body weight, gender, antitherapeutic antibody, albumin, and tumor burden) would require dose adjustment.